Squamous Cell Carcinoma With Bone Invasion: A Systematic Review and Pooled Survival Analysis. Issue 10 (19th October 2022) - Russell, Emma; Udkoff, Jeremy; Knackstedt, Thomas
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Bone invasion has long been recognized as a poor prognostic indicator for cutaneous squamous cell carcinoma (SCC). Survival analyses of factors associated with SCC with bone invasion have not been published. OBJECTIVE: To analyze all published demographic, clinical, and treatment data for SCC with bone invasion and assess the impact of prognostic variables on disease progression, disease-specific death, and overall mortality. MATERIALS AND METHODS: A systematic review and pooled-survival analysis was performed using individual patient data from case reports. Progression-free survival (PFS), disease-specific survival (DSS), and overall survival (OS) were estimated by Kaplan–Meier analysis. RESULTS: The study included 76 cases of SCC with bone invasion from 49 publications. Recurrent tumors and nonsurgical treatment modality were predictors of disease progression in univariable analysis and tumors of the trunk, head, and neck were predictors of disease progression in multivariable analysis. At 5 years from bone invasion diagnosis, patients had a PFS, DSS, and OS rate of 66.7%, 71.7%, and 66.2%, respectively. CONCLUSION: Cases of SCC with bone invasion had poor DFS, DSS, and OS rates, with worse outcomes imparted to tumors of the trunk, head, and neck.